The shadow of totalitarianism action, judgment, and evil in politics - Burdman, Javier, 1983- (SUNY series, intersections : philosophy and critical theory, 2022)
"Examines the relationship of evil, action, and judgment in the work of Immanuel Kant, Hannah Arendt, and Jean-François Lyotard"--